1998
DOI: 10.1042/bj3340617
|View full text |Cite
|
Sign up to set email alerts
|

Structure and organization of the human Theta-class glutathione S-transferase and d-dopachrome tautomerase gene complex

Abstract: The structure and organization of the human Theta-class glutathione S-transferase (GST) genes have been determined. GSTT1 and GSTT2 are separated by approx. 50 kb. They have a similar structure, being composed of five exons with identical exon/intron boundaries. GSTT1 is 8.1 kb in length, while GSTT2 is only 3.7 kb. The GSTT2 gene lies head-to-head with a gene encoding d-dopachrome tautomerase (DDCT), which extends over 8.5 kb and contains four exons. The sequence between GSTT2 and DDCT may contain a bidirecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 43 publications
1
49
0
2
Order By: Relevance
“…Typically, the individual genes for each GST class are clustered together on the same chromosome (23)(24)(25). The fact that no other related sequences were found neither in this chromosomal region nor in other part of the genome seems to indicate that hGSTK1 is the only representative in this GST family in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the individual genes for each GST class are clustered together on the same chromosome (23)(24)(25). The fact that no other related sequences were found neither in this chromosomal region nor in other part of the genome seems to indicate that hGSTK1 is the only representative in this GST family in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence points to transcription of this gene, although the gene product is thought to be inactive. An allele identified in GSTT2 involves a rare p.M139L substitution (Coggan et al, 1998). A phenotype relating to this substitution has yet to be identified, although there is no clear indication that this substitution affects enzyme function (Coggan et al, 1998).…”
Section: Theta Classmentioning
confidence: 99%
“…Coggan et al reported a pseudogene (GSTT2P), which rises from G to T transition at nt 841 (841G>T) in intron 2 of GSTT2 and C to T transition at nt 3255 (3255C>T) in exon 5 of GSTT2P changing 196Arg to a stop codon. In addition a G to A transition at nt 2732 (2732G>A) in exon 4 of GSTT2 was defined that results in substitution of 139Met to 139Ile (Met 139 Ile) (Coggan et al, 1998). However, there is still no clear evidence that the latter SNP may have influence on the enzyme function.…”
Section: Gstt Classmentioning
confidence: 99%